2019
DOI: 10.3390/molecules24213916
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Comparative Therapeutic Potential of Undoped and Nitrogen-Doped Titanium Dioxide Nanoparticles

Abstract: Nitrogen-doped and undoped titanium dioxide nanoparticles were successfully fabricated by simple chemical method and characterized using x-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive x-ray (EDX), and transmission electron microscopy (TEM) techniques. The reduction in crystalline size of TiO2 nanoparticles (from 20–25 nm to 10–15 nm) was observed by TEM after doping with N. Antibacterial, antifungal, antioxidant, antidiabetic, protein kinase inhibition and cytotoxic properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…N-doped TiO2 powder XRD results were found to be strongly dependent on the nitrogen precursor. In the case of ammonia (as in this study) [19], ammonium nitrate [20], and nitric acid [21] as nitrogen precursors, no visible changes in the TiO2 crystal structure were observed; i.e., the N-doped TiO2 crystalline phase was determined by the synthesis conditions (mainly the calcination temperature, which determines the share of anatase and rutile phases), as in the case of undoped TiO2. As a result, no significant differences between N-doped and undoped TiO2 can be seen in the XRD patterns.…”
Section: Catalysts Characterizationmentioning
confidence: 59%
“…N-doped TiO2 powder XRD results were found to be strongly dependent on the nitrogen precursor. In the case of ammonia (as in this study) [19], ammonium nitrate [20], and nitric acid [21] as nitrogen precursors, no visible changes in the TiO2 crystal structure were observed; i.e., the N-doped TiO2 crystalline phase was determined by the synthesis conditions (mainly the calcination temperature, which determines the share of anatase and rutile phases), as in the case of undoped TiO2. As a result, no significant differences between N-doped and undoped TiO2 can be seen in the XRD patterns.…”
Section: Catalysts Characterizationmentioning
confidence: 59%
“…One of the main contributing factors in antibiotic resistance is the formation of biofilms [42]. Therefore, research is shifted to the exploration of antimicrobial potential of metal and metal oxide NPs [43]. Because of their photocatalytic nature and the fact that they are chemically stable, non-toxic, affordable, and Generally Recognised as Safe, TiO 2 NPs have been regarded as an appealing antimicrobial agents [44].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…130,131 Besides, it has been demonstrated that modifying the surface of nanoparticles by nitrogen doping could improve photocatalytic properties, which leads to the enhancement of antifungal and antibacterial characteristic, compared to original nanoparticles. 132,133 Although there are only a few studies of nitrogen-doped nanoparticles on pest control, their applications are expected to be promising for green agriculture. Therefore, we will summarize their current use in controlling phytopathogens, and prove the impact of nitrogen doping on pesticide activity.…”
Section: N-doped Nanoparticles As Nanopesticidesmentioning
confidence: 99%